Enhancing Academic Performance through Digital Capability and Digital Citizenship: Evidence from Business Administration Students - Nanang Adie Setyawan; Andi Setiawan; Suwardi; Saptianing; Destine Fajar Wiedayanti; Dheanda Maurizta Chairunnisa (Politeknik Negeri Semarang, 2026)
The rapid digital transformation of higher education has reshaped learning processes, academic engagement, and student performance. Universities are increasingly required to ensure that students not only possess technical digital skills but also demonstrate responsible and ethical behavior in digital environments. This study aims to examine the influence of digital capability and digital citizenship on academic performance among Business Administration students. A quantitative, causal research design was employed using a cross-sectional survey approach. Data were collected from 120 final-year students of the Business Administration Department at Politeknik Negeri Semarang through a structured questionnaire measured on a five-point Likert scale. Structural Equation Modeling (SEM) with AMOS was utilized to test the proposed model and hypotheses. The results indicate that digital capability has a positive and significant effect on academic performance, while digital citizenship also exerts a positive and significant influence on students’ academic outcomes. The structural model demonstrates good overall fit, and the explanatory power shows that a substantial proportion of variance in academic performance is jointly explained by digital capability and digital citizenship. These findings contribute to the literature by integrating digital competence and ethical digital behavior within a single explanatory framework of academic performance. Practically, the study provides insights for higher education institutions in designing digital learning strategies that enhance both technical capability and responsible digital engagement to improve students’ academic achievement.